TEORI-TEORI BAHASA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Arin Pateka, Philsa; Tihan Arvita; Dini Putri Zahara; Luisha Setia Fernanda; Ahmad Syarif; Silvina Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian language instruction in elementary schools plays a crucial role in developing students’ literacy skills; however, it still faces various challenges, such as low reading and writing proficiency and a lack of active student engagement in the learning process. This study aims to identify, analyze, and examine the relevance of language theories in Indonesian language instruction in elementary schools. The method used was a Systematic Literature Review (SLR) with data sources consisting of scientific journal articles obtained through Google Scholar from 2021 to 2025. Based on a selection process using the PRISMA approach, 10 relevant articles were identified for analysis. The findings indicate that Indonesian language instruction does not rely on a single theory but integrates various theories such as behaviorism, cognitivism, constructivism, cybernetics, and linguistics. Cognitivism and constructivism are the most dominant approaches because they align with students’ cognitive developmental stages and promote active and meaningful learning. However, there remains a gap between the application of theory and actual teaching practices in the field. Therefore, teachers need to master and flexibly integrate various theories to make learning more effective, innovative, and capable of improving students’ literacy skills in the 21st century.